The antigenicity of a plasmodium vivax reticulocyte binding protein-1 (PvRBP1) recombinant fragment in humans and its immunogenicity and protection studies in aotus monkeys (2007)
Plasmodium vivax merozoites have been found to specifically invade immature red blood cells (reticulocytes) and this preference has been associated with two proteins named reticulocyte binding protein-1 and protein-2 (PvRBP1 and PvRBP2). Previous reticulocyte binding assays using 15-mer synthetic peptides spanning the entire PvRBP1 sequence have shown that 25 out of the 195 peptides synthesised (grouped into 4 different regions) displayed high affinity binding to reticulocytes. The PvRBP1 region III (amino acids 1998–2348), encompassing 9 of the previously described high-affinity reticulocyte binding peptides, was expressed as a recombinant protein in the present study. This protein has been shown to be antigenic in humans and it has also been able to induce good humoral and cellular immune responses in Aotus nancymaae monkeys. Despite its high immunogenicity, no protective efficacy was observed in the immunised animals.